2005
DOI: 10.1002/jmri.20279
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine‐induced stress affects intracellular uptake of manganese: A quantitative magnetic resonance imaging study in pigs

Abstract: Purpose: To determine whether there are differences in increase in longitudinal relaxation rate (⌬R1) in the myocardium between bolus administration of Mn 2ϩ ions during rest and during dobutamine-induced stress and, additionally, to determine whether there are differences in ⌬R1 between bolus injection and infusion of Mn 2ϩ ions during dobutamine-induced stress. Materials and Methods:Pigs were divided into three groups with six pigs in each group. All animals received 15 mol MnCl 2 /kg of body weight (b.w.) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Many earlier studies of manganese-enhanced MRI focused on MnCl 2 and MnDPDP, and showed that in rabbit, rat, dog, and pig hearts ⌬R1 increased with the concentration of the administered contrast agent (7,20 -22). The enhancement pattern we observed for MnHPTA is similar to that reported for MnCl 2 in earlier studies that used the same model employed in the present study (20,22). On the other hand, studies in dogs and rats using other models showed a more stable contrast enhancement over the first 30 minutes after injection (23,24).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Many earlier studies of manganese-enhanced MRI focused on MnCl 2 and MnDPDP, and showed that in rabbit, rat, dog, and pig hearts ⌬R1 increased with the concentration of the administered contrast agent (7,20 -22). The enhancement pattern we observed for MnHPTA is similar to that reported for MnCl 2 in earlier studies that used the same model employed in the present study (20,22). On the other hand, studies in dogs and rats using other models showed a more stable contrast enhancement over the first 30 minutes after injection (23,24).…”
Section: Discussionsupporting
confidence: 89%
“…Quantitatively, MnHPTA 15mol/kg increased R1 to a level similar to that observed in a previous study (22) This difference was also observed in a study of mice, in which a comparison of infusion of MnCl 2 at rest and during dobutamine-induced stress revealed a considerable difference in signal intensity (28). For MnHPTA this difference was found only after the 25 mol/kg injection.…”
Section: Discussionsupporting
confidence: 88%
“…Male (n ϭ 4 each) and female (n ϭ 4 each) Kir6.2-KO mice or WT counterparts were anesthetized via intraperitoneal administration of 2,2,2-tribromoethanol (Avertin) at a dose of 250 mg/kg body wt. Under sterile conditions, a heparinized 10-l total volume polyethylene-10 catheter was introduced into the right internal jugular and sutured in place for infusion of the Mn 2ϩ and dobutamine solutions, used for tracing calcium influx and stress induction, respectively (13,19,20,35,56). Anesthesia was then maintained with Ͻ1% inhaled isoflurane to allow for a constant and controllable level of anesthesia and heart rate during the manganeseenhanced cardiac MRI procedure.…”
Section: Dobutamine Stress Under Manganese-enhanced Cardiac Mrimentioning
confidence: 99%
“…Manganese-induced enhancement of the magnetic resonance cardiac signal is indicative of calcium influx into the heart (13,19,20,35). Accordingly, manganese-enhanced cardiac MRI was employed to probe the consequence of K ATP channel deletion on calcium loading under stress in vivo.…”
Section: K Atp Channel Knockout Causes Excessive Cardiac Calcium Strementioning
confidence: 99%
See 1 more Smart Citation